Serum Levels of Homocysteine, Troponin-I, and High Sensitive C-Reactive Protein in Iraqi COVID-19 patients - Sabah Khalid, Shahad; Mohamed Ali, Zahraa; Faris Raheem, Mohanad (Journal of Contemporary Medical Sciences, 2022)
Objective: This study aimed to investigate if the Homocysteine has recently been proposed as a serious predictive biomarker for Covid-19 infection severity. Method: In this case-control study, which involved 90 participants, 5 ml of venous blood specimen was reserved for each participant, to measure homocysteine, troponin-I, and high sensitive C-reactive protein in their blood, to find if there was an association between these markers levels and COVID-19 infection by using STATA version 23. Results: The current study found a significant increase in measured values of homocysteine in patients' serum than controls P-value = 0.004 which is < alpha (0.05) with an area under the curve of 0.678, also found a significant increase in measured values of cardiac troponin-I; and hs-CRP in COVID-19 patients than controls, P-values were 0.02 and 0.00 respectively which are < alpha (0.05) with an area under the curve of 0.686 and 0.739 respectively. Conclusion: Homocysteine has been noted as a strong predictive biomarker for COVID-19 infection severity in many articles, the current study showed that homocysteine had a moderate predictive biomarker for COVID-19 infection. Cardiac troponin-I showed a moderate predictive biomarker for COVID-19 infection, while hs-CRP was noted as a good predictive biomarker. Many studies reported an association between high levels of hs-CRP and mortality rate in COVID-19 patients.